Reverse Engineering of a Hydro Turbine System Mechanical Parts - NofirmanFirdaus; UsdekPanjaitan; Bambang Teguh Prasetyo (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2016)
This paper presents a reverse engineering process for mechanical parts of a hydro turbine system. The parts under reverse engineering (RE) are faceplates and bushings. A glance of reverse engineering process is also presented based on the case study. The key to reverse engineering process is determining the key properties of material. Based on the analysis, there are several material properties that would be used for the comparison with the original equipment.The comparison of the final products with the original components shows that faceplates and bushings manufactured from reverse engineering are equivalent to the original components.